SISTEM INFORMASI PEMANTAUAN STATUS GIZI BALITA - Khasnur Hidjah; Helna Wardhana; Heroe Santoso; Anthony Anggrawan (Universitas Bumigora, 2016)
Based on interviews with staff nutrition Health Offce (Dikes) West Lombok, that is not currently available information systems that can be used to input data monitoring nutritional status of children. So it still takes a very long time to get the right information related to monitoring the nutritional status of children and families aware of nutrition per each district. The primary data sourced directly from the community gathered by Puskesmas offcers. Analysis of the data needed to meet the needs of data input, process and report to the monitoring system of nutritional status include: site identifcation, the identity of the household, the habit of weighing the family members, the question for pregnant or postpartum mothers, the nutritional intake of the family, the identity of a toddler, a child’s weight. The expected benefts of the outcomes defned as follows: enhance the ability to analyze the situation of food and nutrition in every region, able to set the priority handling of food and nutrition, able to monitor and evaluate the development of food and nutrition, improve community health status is marked as well as out of the category of problematic areas of health, especially malnutrition and less.